Capsule endoscopy for small‐intestinal disorders: Current status. Issue 5 (10th February 2019) - Hosoe, Naoki; Takabayashi, Kaoru; Ogata, Haruhiko; Kanai, Takanori
Abstract : Small‐bowel capsule endoscopy (SBCE) is used widely because of its non‐invasive and patient‐friendly nature. SBCE can visualize entire small‐intestinal mucosa and facilitate detection of small‐intestinal abnormalities. In this review article, we focus on the current status of SBCE. Several platforms for SBCE are available worldwide. Third‐generation SBCE (PillCam ® SB3) has a high‐resolution camera equipped with an adaptive frame rate system. Several software modes have been developed to reduce the reading time for capsule endoscopy and to minimize the possibility of missing lesions. The main complication of SBCE is capsule retention. Thus, the main contraindication for SBCE is known or suspected gastrointestinal obstruction unless intestinal patency is proven. Possible indications for SBCE are obscure gastrointestinal bleeding, Crohn's disease, small‐intestinal polyps and tumors, and celiac disease. Colon capsule endoscopy (CCE) can observe inflamed colonic mucosa non‐invasively, and allows for the continuous and non‐invasive observation of the entire intestinal tract (pan‐endoscopy). Recently, application of CCE as pan‐enteric endoscopy for inflammatory bowel diseases (including Crohn's disease) has been reported. In the near future, reading for CE will be assisted by artificial intelligence, and reading CE videos for long periods will not be required.